IMMUNOLOGICAL REACTIVITY IN PATIENTS WITH UROLOGICAL PROFILE UNDER COMBINED THERAPY - A. V. Esipov; A. A. Kostin; A. G. Kochetov; A. S. Esipov; V. V. Parshin; O. Yu. Dmitrieva (Исследования и практика в медицине, 2017)
Prevention and treatment of postoperative purulent-inflammatory complications in urological practice remains a subject for study and improvement in all medical centers. The principle of evidence must be taken as a basis of effectiveness of therapy. In this study the quality criteria of demonstrated therapy are immunological parameters.The purpose of this study is to identify the effectiveness of using monooxidase (NO) containing a gas stream replenishing the deficiency of endogenous NO in a group of patients; and to investigate immunological reactivity in patients under complex therapy included nitrogen monoxide and immunomodulators.Materials and methods. In this experimental study we determined the functioning of the main links of the patient’s immunological system. They were determined on the basis of the levels of general T-lymphocytes (T-total), T-helper (T-h), T-suppressor (T-s), natural killer (NK), B-lymphocyte and immunoglobulin G, M, A, circulating immune complexes (CIC).Results. Based on the obtained data, we concluded that the traditional treatment of patients with postoperative complications was less effective than the one proposed in our study. Immunological picture of patient’s condition come back to normal almost from the first day of treatment, and under traditional treatment it was only on the 7th day. Under using complex treatment with nitrogen monoxide, parameters of humoral immunity corresponded to the norm already on the 7–14th day from the beginning of treatment.Conclusion. NO-containing gas flow application in complex prevention of purulent-inflammatory complications made possible to eliminate wound infection in shorter terms and to shorten the period of patient’s hospitalization. The best results were obtained in terms of immunological reactivity in a clinical trial in patients who received complex therapy included nitrogen monoxide and lymphotropic administration of the immunomodulators.